PERAN POLA ASUH ORANGTUA PADA PEMBERIAN PENDIDIKAN SEKS PADA ANAK USIA DINI - Aisyah, Aisyah; Aulia Insani; Denisa Ofel Anglelita; Dian Mustachin Nurjannah (Journal of Innovation Research and Knowledge, 2023)
Sexual education is a basic science about sexuality which is very important for early childhood so that children can adapt to the surrounding environment and protect themselves from the surrounding environment or other people they do not know. The introduction of sexual education for early childhood cannot be separated from the role of parenting style. The introduction of sexual education can be introduced in different ways, each parent has a different parenting style so that it has a different impact on the introduction of sexual education. This research was conducted to find out how the role of parenting influences the introduction of sexual education in children aged 4-5 years. The research method used is descriptive qualitative by collecting data through observation, interviews and documentation. Then, the subjects of this study were 3 children who had democratic, authoritarian and permissive parenting styles. Informants taken were 3 people who were parents, siblings and grandmothers who helped care for the object. Based on the research that has been done, the results show that the type of parenting applied by parents causes differences in behavior towards knowledge of sexual education in children aged 4-5 years. The permissive parenting style used has more positive impacts than authoritarian and democratic parenting styles. The development of this research found that the number of children in the family, how to communicate and negative perceptions related to sexual education.